DAMPAK KEBERADAAN INDOMARET DAN ALFAMIDI TERHADAP PENDAPATAN USAHA WARUNG (KIOS) DI KELURAHAN SASA DAN JAMBULA - Renjaan, Datje; Rusli, Rosalita Sari M (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2023)
This research aims to determine the impact of the existence of Indomaret and Alfamidi on the income of stall businesses in Sasa and Jambula sub-districts. This research uses a qualitative descriptive approach. The sample used in this research was 20 respondents divided into 10 consumers and 10 stall entrepreneurs located in 2 sub-districts. The sample was taken using a purposive sampling technique, data collection in this research: taken through observation, interviews (interview), Documentation (document). The research results show that the existence of Indomaret and Alfamidi has a negative impact on the income of stall entrepreneurs, where there is a decrease in income of 30% to 60%. There was only 1 respondent who was not affected. The research results also explain that the decline in income was caused by several factors, namely location, service, facilities which encourage consumers to refine their choice of shopping at Indomaret and Alfamidi.